Mosses of Trus Madi, Sabah, Malaysia - Monica Suleiman; Edwards, S. R. (2002)
Abstract. A species list of mosses collected in Mt. Trus Madi, Sabah, between 10 September and 10 October 1996 is presented. A total of 153 taxa were collected, of which 11 are new to Borneo and five new to Sabah.